2011
DOI: 10.1007/s00376-010-0045-9
|View full text |Cite
|
Sign up to set email alerts
|

Middle stratospheric polar vortex ozone budget during the warming Arctic winter, 2002–2003

Abstract: The ozone budget inside the middle stratospheric polar vortex (24-36 km) ) is used to analyze the observed variation in polar vortex ozone during the stratospheric sudden warming (SSW) events. Both MIPAS measurement and MOZART-3 calculation show that a pronounced increase (26-28 DU) in the polar vortex ozone due to the SSW events. Due to the weakening of the polar vortex, the exchange of ozone mass across the edge of the polar vortex increases substantially and amounts to about 3.0 × 10 7 kg according to MO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…This is due to the long life time of odd oxygen in the lower stratosphere and to the small meridional mixing of the polar air masses. A simulation of Liu et al (2011) for the SSW in Arctic winter 2002-2003 gave the result that horizontal advection of ozone into the polar vortex increases significantly due to the weakening of the vortex by planetary waves. They found a pronounced in-…”
Section: Composites Of Total Ozone Columnmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the long life time of odd oxygen in the lower stratosphere and to the small meridional mixing of the polar air masses. A simulation of Liu et al (2011) for the SSW in Arctic winter 2002-2003 gave the result that horizontal advection of ozone into the polar vortex increases significantly due to the weakening of the vortex by planetary waves. They found a pronounced in-…”
Section: Composites Of Total Ozone Columnmentioning
confidence: 99%
“…Flury et al (2009) studied the response of the atmospheric composition to a SSW and found ozone depletion and polar stratospheric clouds over Europe. Liu et al (2011) performed an ozone budget analysis and found that ozone inside the polar vortex is enhanced by 26-28 DU due to the SSW. Baldwin and Dunkerton (2001) reported that SSWs cause anomalous weather regimes 60 days after the SSW in the troposphere.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of ozone is affected by changes in both chemistry and dynamics during the SSW events over the Northern Hemisphere. The short-term changes in stratospheric ozone in response to SSWs have been rather extensively studied using ground-based, in situ and satellite observations [37] [47]- [50]. In this paper the response of the TCO with five different SSWs events were considered to understand the variation of total column ozone over the polar and middle latitude region of the Northern hemisphere.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of a SSW on the ozone, hydroxyl distribution and water vapor in the mesopause region has been simulated [36]. The contributions of both chemistry and dynamics to polar vortex ozone at 24 -36 km during the 2002-2003 SSW was quantified using measurements by the MIPAS instrument on board the Envisat satellite and the MOZART-3 chemical transport model [37]. In this paper five major SSWs events were considered to study the variability of total column ozone over the polar and middle latitude regions.…”
Section: Introductionmentioning
confidence: 99%
“…MOZART-3 has been used and evaluated in a number of studies (e.g., Gettelman et al, 2004;Kinnison et al, 2007;Kulawik et al, 2006;Liu et al, 2009Liu et al, , 2011Park et al, 2004). The model simulates the atmosphere from the surface to 0.001 Pa level (∼ 115 km) by dividing it vertically into 60 layers.…”
Section: Model Descriptionmentioning
confidence: 99%